Saudi Arabia as a Regional Power and an Absolute Monarchy Undergoing Reforms. Vision 2030 – the Perspective of the End of The Second Decade of the 21st Century - Czornik, Katarzyna (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The research objective of this paper is an analysis of the determining factors which allow Saudi Arabia at the end of the second decade of the 21st century to hold the position of a regional power and to maintain it at least in the medium-term perspective. This paper also aims at an analysis of the potential effectiveness of the reforms which have been implemented by the authorities in Riyadh in order to build a new, modified image of the feudal monarchy – Saudi Arabia as an enlightened (but permanently absolute) monarchy undergoing reforms. The hypothesis formed in this paper is as follows: Saudi Arabia at the end of the second decade of the 21st century is a regional power and an absolute monarchy undergoing reforms, which intends to build a new, positive and friendly image of the kingdom by way of reforms introduced in the economic, political and social spheres. The reforms, however, actually take place only at the economic level, which results from the fact that they do not undermine the foundations of the sharia law and the doctrine of Wahhabism. In the political and social spheres the reforms are just a façade. The methods used in this paper include: content analysis, systemic analysis and comparative method. The findings: the hypothesis posed above has been verified positively. Saudi Arabia at the end of the second decade of the 21st century is a regional power and an absolute monarchy undergoing reforms, which intends to build a new, positive and friendly image of the kingdom in the international community through introduction of reforms. The reforms undertaken within the framework of the Vision 2030 initiative are revolutionary, but actually they take place only in the economic sphere. However, in the political and social spheres – especially as regards granting further privileges and rights to Saudi women – although they are extremely important and even of breakthrough character and the very fact of their existence should be recognised, in reality they are only a façade and their implementation meets resistance not only from a part of political elites and radical clergy but also from the society itself, which is not mentally prepared for such changes.

Celem badawczym niniejszego artykułu jest dokonanie analizy determinant, które sprawia¬ją, że Arabia Saudyjska u schyłku drugiej dekady XXI wieku posiada i w perspektywie co naj¬mniej średnioterminowej utrzyma pozycję mocarstwa regionalnego. Celem jest również analiza potencjalnej efektywności reform, które wprowadzają władze w Rijadzie, na rzecz zbudowa¬nia nowego, zmodyfikowanego wizerunku feudalnej monarchii, jaką jest Arabia Saudyjska, na rzecz reformującej się i oświeconej monarchii (aczkolwiek permanentnie absolutnej). Hipoteza postawiona w niniejszym artykule, brzmi następująco: Arabia Saudyjska u schyłku drugiej de-kady XXI wieku to mocarstwo regionalne i reformująca się monarchia absolutna, która poprzez wprowadzane reformy w sferach ekonomicznej, politycznej i społecznej zmierza do zbudowa¬nia nowego pozytywnego i przyjaznego wizerunku królestwa. Reformy faktycznie zachodzą jednak tylko w płaszczyźnie ekonomicznej, co wynika z faktu, iż nie godzi to w podstawy prawa szariatu i zasady wahabizmu. W płaszczyznach politycznej i społecznej, reformy mają tylko charakter fasadowy. Metody wykorzystane w artykule to analiza treści, analiza systemo¬wa, jak również metoda komparatywna. Dokonane ustalenia: hipoteza postawiona na wstępie została pozytywnie zweryfikowana. Arabia Saudyjska u schyłku drugiej dekady XXI wieku to mocarstwo regionalne i reformująca się monarchia absolutna, która poprzez wprowadzane re-formy zmierza do zbudowania nowego pozytywnego i przyjaznego wizerunku w społeczności międzynarodowej. Reformy w ramach Vision 2030 są rewolucyjne, ale faktycznie dokonują się tylko w sferze ekonomii. W płaszczyznach politycznej i społecznej – zwłaszcza w materii przyznawania Saudyjkom kolejnych przywilejów i praw – mimo iż są niezwykle istotne, a na-wet przełomowe i należy docenić sam fakt ich zaistnienia, to jednak mają charakter fasadowy i jedynie wizerunkowy, a ich implementacja napotyka nie tylko na opór części elit politycznych, radykalnych duchownych, ale również saudyjskiego społeczeństwa mentalnie nieprzygotowa-nego do takich zmian.
Arabia Saudyjska jako mocarstwo regionalne i reformująca się monarchia absolutna. Vision 2031 Initiative – perspektywa z końca drugiej dekady XXI wieku
Keywords: Saudi Arabia; feudal monarchy; transformation; Vision 2030; Arabia Saudyjska; monarchia feudalna; transformacja; Vision 2030